Efektifitas Pengelolaan Retribusi Pasar Sebagai Sumber Pendapatan Asli Daerah Dan Upaya Penanggulangan Penyimpangan - Frans Simangunsong; Hervina Puspitosari (Jurnal Risalah Hukum, 2021)
Developments organized by these regions are regional in nature, as a realization of development planning in accordance with development priorities at the regional level as part of the implementation of autonomous government decentralization. In order to support the implementation of economic development goals in the regions, local governments are required to have the ability to meet the needs of these regional expenditures, namely by optimizing local revenue (PAD). is the establishment of a retribution policy through an accountable collection system with the use of information technology so that it is easily controlled and supervised by all parties and transparent that can be accountable to the public through the application of a book system that can be monitored by all parties, providing strict sanctions in accordance with the laws and regulations. applicable regulations as well as applicable regional regulations related to taxes and levies in order to provide a deterrent effect for those who abuse their authority. The need for supervision of officers in the field. Local governments that do not yet have electronic-based retribution services need to immediately prepare electronic services in collecting market retributions through e levies in the context of efficient, transparent and accountable management of market retributions. Increased supervision of the Regional Government in the management of user fees so that it is optimal in providing income for Regional Original Income and the realization of a prosperous society and good governance Keywords: market levy, locally-generated income, deviation countermeasures